2023
DOI: 10.1155/2023/5543234
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Level of DKK-1 as a New Bone Formation Factor in Patients with Early Spondyloarthritis

Yuliasih Yuliasih,
Aghnia Permatasari,
Lita Diah Rahmawati
et al.

Abstract: The role of dickkopf-related protein 1 (DKK-1) in radiographic development may become a robust marker for early spondyloarthritis (SpA) diagnosis. This study aimed at determining the serum DKK-1 profile in patients with SpA and investigating its relationship with SpA progression. Supported by analyzing the BMD data which aims to affirm the potential of DKK-1 as a biomarker for early diagnosis of SpA, this research may become the early study to produce a robust tool to diminish the fatal impacts in SpA. This cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As shown in our findings, we identified 38 SpA patients, with the majority were female. In our prior research, we also documented a prevalence of females in patients with SpA, where the male-to-female ratio stood at 15:16 (Yuliasih et al, 2023). The SpA typically initiates during the second or third decade of life, onset after the age of 50 reported to be rare.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As shown in our findings, we identified 38 SpA patients, with the majority were female. In our prior research, we also documented a prevalence of females in patients with SpA, where the male-to-female ratio stood at 15:16 (Yuliasih et al, 2023). The SpA typically initiates during the second or third decade of life, onset after the age of 50 reported to be rare.…”
Section: Discussionmentioning
confidence: 86%
“…Monti et al (2017) stressed the importance of ASDAS-CRP as a strict disease activity index for "treat to target" approaches to prevent inactive disease with fibromyalgia-like symptoms. Yuliasih et al (2022Yuliasih et al ( , 2023 found a correlation between ASDAS-CRP levels and IL-17. Zhang et al (2022) suggested that ASDAS based on ESR might be superior, and Ramiro et al (2013) demonstrated ASDAS-CRP's better prediction of radiological changes than BASDAI.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal elevation of Dkk1 in patients with PsA and RA is thought to be involved in the process of structural radiographic alterations and the development of bone erosion [55,56]. In addition, Dkk1 has been identified as a possible diagnostic marker for early PsA, and its levels are higher in early PsA compared to established PsA [57].…”
Section: Discussionmentioning
confidence: 99%